The influence of product quality, prices, and promotions on buyer decisions in the small and medium industry handicrafts of Tanjungpinang City - Zairina, Syarifah; Wibisono, Cablullah; Ngaliman, Ngaliman; Indrayani, Indrayani; Satriawan, Bambang (Journal of Multidisciplinary Academic Business Studies, 2023)
Purpose: This study aims to analyze the impact of promotions, pricing, and product quality on consumer choices in Tanjungpinang City's small and medium-sized handicraft industry. It seeks to understand how these factors influence consumer decision-making and subsequent purchases. Research Methodology: The research employed a quantitative approach with a census sampling technique, involving 145 respondents of Tanjungpinang City’s handicraft consumers. Data were collected using questionnaires and analyzed with Structural Equation Modeling (SEM) using SmartPLS version 4, focusing on product, price, promotion, service quality, and purchase decisions. Results: The findings revealed the significance of these relationships: competence Findings reveal that product quality significantly and positively influences purchase decisions, while price shows a very significant positive effect. Conversely, promotion has no significant effect on consumer decision-making. Service quality also acts as a mediator, strengthening the relationship between product and price with purchasing decisions. Conclusions: Price and product quality are key determinants of consumer purchasing behavior in Tanjungpinang’s handicraft sector, whereas promotions play a marginal role. Service quality emerges as a crucial mediating factor that enhances the influence of product and price on consumer decisions. Limitations: udy is limited by the use of a single industry and location, relatively small samples, and reliance on survey data without qualitative triangulation, which may restrict the generalizability of findings. Contribution: The research contributes to understanding consumer behavior in the handicraft SME sector by highlighting the mediating role of service quality. It provides practical insights for entrepreneurs to prioritize product quality and pricing strategies, while using promotions more effectively to strengthen market competitiveness.